Peran koperasi Sekolah dalam menumbuhkan Jiwa kewirausahaan terhadap peserta didik di SDN 02 Sawangan - Handiawan, Davy; Hikmawati, Yusnita; Setiani, Anggun; Abidah Maryam, Farah; Kusumaningtyas, Dyah; Rahmawati, Ferida (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Entrepreneurship education is crucial in shaping students' creativity, innovation, and management skills to become successful entrepreneurs. School cooperatives are a strategic platform that can effectively instill entrepreneurial values ​​in schools, in addition to serving their needs. This article examines the role of school cooperatives at SDN 02 Sawangan in fostering students' entrepreneurial spirit through practical learning such as small business management, financial management, and hands-on decision-making. A qualitative descriptive research method was used to explore the cooperative's role as a real-life entrepreneurial laboratory that fosters a sense of responsibility, discipline, and independence from an early age. The results show that school cooperatives contribute to shaping entrepreneurial character, fostering economic awareness, and enhancing students' entrepreneurial skills, thus preparing them to face the challenges of the business world in the future. This paper emphasizes the importance of revitalizing and optimizing the function of school cooperatives as a means of applicable and contextual entrepreneurship education.